REVERSED-PHASE HPLC RETENTION OF DEOXYRIBONUCLEOSIDES AS A FUNCTION OF MOBILE-PHASE COMPOSITION - LEE, YW; ROW, KH; SO, MS; POLUNINA, IA; LARIN, AV (MARCEL DEKKER INC, 1995)
Comparison of approaches describing retention of deoxynucleosides (dCyd, dUrd, dGuo, dThd, and dAdo) as a function of the mobile phase composition has been performed. The volume fraction (F) of organic modifier was changed from 0.05 to 0.30, and to 0.12 for methanol and acetonitrile, respectively. Linear regression has been carried out for the following equations: log k' = log k'(w) - S X F (1), log k' = H + Klog(1/F) (2), k' = A + B(1/F) (3), where k' is capacity factor, and log k'(w), S, H, K, A and B are experimental coefficients. The best fits mere obtained for the eqns. (1) and (3), and the poorest correlations were obtained for eqn. (2). The Slope ratios B-methanol/B-acetonitrile and S-acetonitrile/S-methanol are changed in comparatively narrow ranges with average values of 2.86 and 2.30, respectively. Unlike the slope S of eqn. (1), the slope B of eqn. (3) can characterize the properties of solute and organic modifier simultaneously. For each solute, the intercepts A calculated for acetonitrile and methanol as organic modifiers are coincident closely. It is shown the validity of the coefficients of eqn. (3) to express the deoxyribonucleoside properties.
Keywords: PERFORMANCE LIQUID-CHROMATOGRAPHY